Rebuilding the Left - Harnecker, Marta (Zed Books ; Distributed in the USA exclusively by Palgrave Macmillan, 2007)
Based on a lifetime's experience in politics, this book is a critique of social democratic realpolitik. It studies the challenges faced by the left now, and suggests ways to move forward to build a different world. The author looks to the social experiments being carried out in Latin America today: they are essentially socialist, democratic projects in which the people are the driving force. Rebuilding the Left offers real hope to those who believe that an alternative to capitalism is necessary and possible.